(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2025)
This study examines the security of cloud computing management infrastructures from the perspective of the insider attacker. It is also proposed to design and implement a security system for the infrastructures responsible for the management of cloud computing environment against the insider attacker. To achieve this aim, we designed a security solution that handles login verification and login information storage. The application stores the login information of every personnel who has been defined to access the system. The solution also stores information about infrastructure managers, the host server, the virtual server, the smart routers and switches, all of which are used for storage and transmission of data over the internet. The infrastructural security solution is applicable to Infrastructure as a service (IaaS). The system is also capable of handling authentication of cloud members, verification and monitoring of data transfer, thus maintaining network security for our cloud environment and data confidentiality. The security system also provides the administrator with the privilege of monitoring who is logged into the cloud environment, in other to protect the network from hackers. Because design method is required to complete this research, Waterfall Design Methodology was adopted for the research, design and implementation methodology. Programming is performed using PHP, coding is done using HTML platform, Couchbase offline server is used as our local server for hosting this cloud network security system, and advanced network security Standard algorithm is implemented for ensuring security framework.